Mitchell, Barbara. Photograph of Joan Doherty, Mary Ann Druken, and Cecilia Doherty from Barbara Mitchell's personal photograph collection. - Jarvis, Dale
Left to right: Joan Doherty, Mary Ann Druken, and Cecilia Doherty outside of Department of Transport.